Mapping the Landscape: A Bibliometric Analysis of Global Trends in Sustainable Performance - Shafi, Roslina Mohamad; Shahid, Waseem; Osman, Ismah; Arifin, Nur Afizah Muhamad (International Review of Management and Marketing, 2025)
The study primary objective is to trace the evolution of research on sustainable firm performance. By providing a comprehensive overview of key trends and developments in this field, the study seeks to contribute to the existing body of literature and offer valuable insights into the progression of sustainable performance research. A bibliometric analysis was conducted using selected publications from the web of science core collection (WoSCC) database, covering the period from 2010 to 2024. VOSviewer software was employed to perform the analysis. The findings of this study present several important implications. It highlights the evolution of sustainability-related literature across various academic journals and identifies the most pertinent topics concerning firm sustainable performance. The study also identifies the most frequently cited papers and outlines potential areas for future research. Notably, the analysis reveals a literature gap in the assessment of firms’ social and environmental performance, suggesting that this area warrants further scholarly attention in the coming years. Additionally, the study emphasizes the need for enhanced collaboration between academia and industry to bridge the gap between research and practical application.